2021
DOI: 10.3389/fmolb.2021.697149
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage to RNA is Altered by the Presence of Interacting Proteins or Modified Nucleosides

Abstract: Oxidative stress triggered by the Fenton reaction (chemical) or UVR exposure (photo) can damage cellular biomolecules including RNA through oxidation of nucleotides. Besides such xenobiotic chemical modifications, RNA also contains several post-transcriptional nucleoside modifications that are installed by enzymes to modulate structure, RNA-protein interactions, and biochemical functions. We examined the extent of oxidative damage to naturally modified RNA which is required for cellular protein synthesis under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…2, B), with the biotin labeling reaction generating a mean specificity ratio of approximately 94-fold and the anti-8-oxoG antibody generating a mean specificity ratio of approximately 67-fold. We further tested cross-reactivity for the biotin labeling reaction towards labeling another oxidation-related purine RNA modification, 8-oxo-7,8-dihydroadenine (8-oxoA) [43]. Despite the structural similarity between 8-oxoA and 8-oxoG, as well as their similar redox potentials [12], we noted a relatively low, approximately 2-fold labeling preference for 8-oxoA over unmodified RNA (Supp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2, B), with the biotin labeling reaction generating a mean specificity ratio of approximately 94-fold and the anti-8-oxoG antibody generating a mean specificity ratio of approximately 67-fold. We further tested cross-reactivity for the biotin labeling reaction towards labeling another oxidation-related purine RNA modification, 8-oxo-7,8-dihydroadenine (8-oxoA) [43]. Despite the structural similarity between 8-oxoA and 8-oxoG, as well as their similar redox potentials [12], we noted a relatively low, approximately 2-fold labeling preference for 8-oxoA over unmodified RNA (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…Relative to in vitro conditions, we expected that the natural protective mechanisms of the cells would contribute to more realistic (i.e. likely lower) levels of RNA oxidation accumulation [43]. Herein, we cultured K-12 wildtype E. coli to mid-log phase (OD 600 = 0.5-0.6) in LB media and then added increasing concentrations of H2O2 (0-20 mM) to induce oxidative stress for 20 minutes at 37°C; these conditions were selected based on previous work in our lab (unpublished data) which found that 20 mM H2O2 exposure at 37°C for 20 minutes resulted in 40-60% survival for K-12.…”
Section: Resultsmentioning
confidence: 99%
“…The tertiary structure of tRNAs, including intermolecular base-pairing, likely limits the number of nucleoside residues for reaction. While beyond the scope of this work, it would be of interest to perform RNA modification mapping [46] to identify whether specific regions of tRNAs are more prone to BPDE adduction than others in a manner similar to that found for oxidative damage of RNAs [47]. to the one after tRNA exposure (Figure 9c).…”
Section: Lc-ms-based Characterization Of Modified Ribonucleoside-bpde...mentioning
confidence: 92%
“…Molecularly, ROS are formed from a cascade of chemical reactions within cells ending with the production of a hydroxyl radical. This cascade consists of enzymatic reactions, enzymatic auto-oxidation events (where an electron is accidentally transferred from various enzymes like dehydrogenases and glutathione reductase to dissolved oxygen), and the inorganic Fenton reaction with iron in solution (11,12,15,(22)(23)(24)(25) (Figure 1c). These hydroxyl radicals are the most reactive of the ROS, causing nonspecific oxidation of biomolecules, making them the most toxic to the cell.…”
Section: Exposure To Oxidative Stressmentioning
confidence: 99%
“…The native susceptibility of all classes of RNA to oxidative stress is due mainly to oxidative chemical modifications of the RNA bases themselves. The most common RNA modification in response to oxidative stress is 8-hydroxyguanosine (8-oxo-G), an oxidized form of guanosine (12,25,52,53). In E. coli, global levels of 8-oxo-G have been observed to increase approximately fourfold when exposed to 1 mM hydrogen peroxide and tenfold under 5 mM hydrogen peroxide; for reference, the percent viability measured in E. coli colony-forming units remaining after 30 min is 92% under 1 mM hydrogen peroxide and 58% under 5 mM hydrogen peroxide (27).…”
Section: Potential For Rnas As Chemical Sensors Of Oxidative Stressmentioning
confidence: 99%